2010
DOI: 10.1007/s00259-010-1541-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of coronary endothelial function with generator-produced 82Rb PET: comparison with 15O-labelled water PET

Abstract: Purpose Endothelial dysfunction is the earliest abnormality in the development of coronary atherosclerosis. Rb PET may be applicable for risk assessments or evaluation of risk factor modification in subjects with coronary risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
(130 reference statements)
2
35
0
Order By: Relevance
“…Yoshinaga et al recently demonstrated that MBF measurement by 82 Rb PET/CT using the same 2-compartment model was comparable with MBF measurement by 15 O-water, which is the gold standard for the assessment of MBF. 38 This technique allows assessment of endothelium-dependent coronary vasomotion, which can be impaired by cardiovascular risk factor such as diabetes, 39,40 smoking, 41,42 hypercholesterolemia 43,44 or menopause. 45 Moreover, it provides information about epicardial coronary artery stenosis or diffuse microvascular disease, which may decrease the MFR and affect the response to CPT.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshinaga et al recently demonstrated that MBF measurement by 82 Rb PET/CT using the same 2-compartment model was comparable with MBF measurement by 15 O-water, which is the gold standard for the assessment of MBF. 38 This technique allows assessment of endothelium-dependent coronary vasomotion, which can be impaired by cardiovascular risk factor such as diabetes, 39,40 smoking, 41,42 hypercholesterolemia 43,44 or menopause. 45 Moreover, it provides information about epicardial coronary artery stenosis or diffuse microvascular disease, which may decrease the MFR and affect the response to CPT.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers showed reduced MBF response during the CPT using 82 Rb, which was similar to the MBF response observed using 15 Olabeled water as a standard measurement. 21 That study suggests that 82 Rb PET is applicable for risk assessments or evaluation of risk factor modification in subjects with coronary risk factors. This approach was confirmed by another group.…”
Section: Cptsmentioning
confidence: 99%
“…82 Rb is produced from a strontium-82 ( 82 Sr)/ 82 Rb generator and is widely used in centers without immediate access to a cyclotron. 20, 21 Recently introduced 18 F-labeled perfusion tracers have a relatively longer half-life (110 min), which means they could possibly be delivered from pharmaceutical companies to hospitals.…”
Section: Mbf Quantification With Petmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some cardiovascular centers in Japan and Europe have begun 82 Rb studies. 38 Thus, PET MPI using 82 Rb could be widely available shortly.…”
Section: Overcoming Technical Disadvantagesmentioning
confidence: 99%